Implementation of the Islamic Spirituality Programme in Realising the Learning Objectives of Islamic Religious Education at State Elementary School 1 Jenggolo Malang - Sujatmiko, Andri; Musnandar, Aries (Yayasan Adra Karima Hubbi, 2024)
Learning Islamic Religious Education (PAI) is an important part of what is mentioned in Law no 20/2003 of the National Education System aims to develop the potential of students to become human beings who are faithful and devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, skilled, independent, honest, and become democratic and responsible citizens. So that all efforts to realise learning objectives are very interesting to research. One of these efforts is the implementation of the Islamic Spirituality programme at State Elementary School 1 Jenggolo Kepanjen Malang. The research method uses descriptive qualitative which is natural and displayed as it is. The results showed that the existence of Islamic Spirituality is needed because it can form religious character and social care, including; 1) The habituation of prayer and the fulfilment of fardhu, sunnah and religious activities form the character of students who are disciplined on time and hasten obligations; (2) The habituation programme of smiles, greetings and salutations makes students have good social relations between fellow students and teachers; (3) Islamic Spirituality programmes form students to be more tolerant, respect differences and pay attention to the environment.